2005
DOI: 10.7326/0003-4819-142-4-200502150-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Combination Therapy for Chronic Hepatitis B: Comparing Pegylated Interferon-α2b and Lamivudine with Lamivudine Alone

Abstract: In patients with HBeAg-positive chronic hepatitis B, staggered combination treatment with pegylated interferon-alpha2b and lamivudine may lead to a higher rate of virologic response than lamivudine monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
224
1
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(250 citation statements)
references
References 33 publications
15
224
1
10
Order By: Relevance
“…The development of pegylated IFNs with improved pharmacokinetics has been shown to yield a better efficacy and convenience than the conventional IFNs in the treatment of chronic hepatitis C. [41][42][43][44][45] Regarding the treatment of chronic hepatitis B, recent pilot trials also demonstrated that pegylated IFN was more effective than conventional IFN or other nucleotide/nucleoside analogues in either HBeAg-positive or -negative chronic hepatitis B. 8,10,15,25,45 Whether pegylated IFN-based therapy in combination with other antiviral agents such as ribavirin could enhance the treatment efficacy in patients with chronic hepatitis B awaits further clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of pegylated IFNs with improved pharmacokinetics has been shown to yield a better efficacy and convenience than the conventional IFNs in the treatment of chronic hepatitis C. [41][42][43][44][45] Regarding the treatment of chronic hepatitis B, recent pilot trials also demonstrated that pegylated IFN was more effective than conventional IFN or other nucleotide/nucleoside analogues in either HBeAg-positive or -negative chronic hepatitis B. 8,10,15,25,45 Whether pegylated IFN-based therapy in combination with other antiviral agents such as ribavirin could enhance the treatment efficacy in patients with chronic hepatitis B awaits further clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,15,25,45 Whether pegylated IFN-based therapy in combination with other antiviral agents such as ribavirin could enhance the treatment efficacy in patients with chronic hepatitis B awaits further clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…PegIFN-a therapy results in HBeAg seroconversion rates of up to 32% and 48%, respectively, when assessed at weeks 24 and 48 post-treatment [43][44][45][46] and sustained after cessation of therapy in the majority (80-90%) of HBeAgpositive patients [47]. Baseline HBV and ALT levels are predictive factors for HBeAg seroconversion [47].…”
Section: Treatment-induced Hbeag Seroconversion and Disease Progressionmentioning
confidence: 99%
“…62 One way to use the serum HBV-DNA as a predictor of response during treatment is to establish a withdrawal rule. In a combined post hoc analysis of two clinical trials using a combination of PEG-IFN alpha-2b and lamivudine in HBeAg-positive patients with chronic hepatitis B, 52,59 failure to decrease HBV-DNA to 10,000 copies/mL as early as in week 8 has a negative predictive value of 92% for SVR. 60 Based on the data of a randomized international study using PEG-IFN alpha-2a as monotherapy, a much higher cutoff, of 9 log copies/mL in week 24, was described as presenting a negative predictive value of 86% for sustained seroconversion of HBeAg.…”
Section: Serum Hbv-dnamentioning
confidence: 99%
“…59,67 In 26 HBeAg-positive patients that completed the combined treatment of PEG-IFN alpha-2b for 32 weeks and lamivudine for two years, a level of HBsAg < 1,500 UI/ mL presents 71% sensitivity and 84% specificity to predict SVR. 51 In an international study with PEG-IFN alpha-2a, in HBeAg patients, a level < 10 UI/mL in week 48 and decline during the treatment > 1 log UI/mL can predict a sustained disappearance of HBsAg three years after the use of PEG-IFN alpha-2a, with or without the concomitant use of lamivudine.…”
Section: Quantitative Hbsagmentioning
confidence: 99%